Case study: lessons learned from a community-based early frailty intervention programme in Singapore - Jayaprakash, Kamala Priya; Ngo, Rachel; Lee, Elianna; Chng, Pey Ling; Lee, Hengky; Chua, Salan; Lee, Deborah; Wong, Carina; S, Viknessh (Frontiers in Public Health, 2024)
Frailty is a dynamic and evolving state of health which involves the gradual loss of physiological in-built reserves. In Singapore, there is growing interest in delivering frailty intervention programmes at scale in the community to meet the demands of an ageing population. New methods of programme delivery such as community-led models that do not rely on healthcare professional manpower are critical to address this unmet need. In this paper, we describe our experience and some lessons learned from the implementation of a communitybased early frailty intervention programme for older adults, delivered for the first time by trained laypersons.From August to September 2022, 'Steady Lah', a community-based early frailty intervention programme with physical activity and nutrition-based elements, was conducted at an Active Ageing Centre in Singapore. A total of 23 participants with mean age of 73.8 years were enrolled in the 12-session programme comprising of progressive strength and balance-based exercises and workshop-based learning focusing on nutrition.In the implementation of this run of 'Steady Lah', modifications were made from a healthcare professional-led model to a trained layperson-led model with additional steps taken to ensure participant safety and assess overall effectiveness when delivered by trained laypersons. Good collaboration between stakeholders in healthcare institutions and the community is necessary to co-develop a model that prioritises the needs of the frail older adults.